Poor Women's Education Under Welfare Reform - Barbara Sparks (Adult Education Research Conference, 1999)
This paper reports the effects welfare reform has on the educational development of 48 single mothers in the Midwest. Findings indicate academic tracking into low skill vocational training programs, the lack of knowledge women have about their rights under Temporary Assistance for Needy Families (TANF), and factors which contribute to low educational attainment.